10 Animal Welfare Research Perspectives and Opportunities for the United States Swine Industry. (10th April 2018) - Webb, S
Abstract: The National Pork Board is the national checkoff organization and is responsible for education, research and promotion efforts on behalf of U.S. pig farmers. The National Pork Board Animal Welfare committee is comprised of producers, academia, packers, and allied industry and is responsible for carrying out the Pork Checkoff research mission related to animal welfare and animal care. Each year, the group establishes research priorities, issue request for proposals, and determine which proposals to fund. Current research priorities include management of compromised pigs and timely euthanasia, painful procedures and pain management, aggressive and damaging behaviors, and farrowing housing. It is important that research projects be multidisciplinary in their approach and should include neuroscience, performance, physiology, and behavior when applicable. In addition to National Pork Board, animal welfare research funding is available through government agencies such as the US Department of Agriculture's National Institute for Food and Agriculture, Agriculture Research Service, and the Foundation for Food and Agriculture Research.